The effects of trade liberalization on skill acquisition: a systematic review. Issue 2 (17th June 2019) - Sun, Sharon Zhengyang; MacIsaac, Samuel; Duclos, Buck C.; Lilly, Meredith B.
Abstract : Purpose: The benefits of trade liberalization on upskilling and skill-based wage premiums for high-skilled workers have recently been questioned in policy circles, in part because of rising income inequality and populist movements in developed economies such as the USA. The purpose of this paper is to determine the effects of trade liberalization on the relative supply and demand for skills. Design/methodology/approach: Through the systematic review of the literature on trade and skill acquisition, this paper isolates a total of 25 articles published over the past two decades. Findings: Key findings demonstrate the importance of the relative development of the trading partner, with more developed countries experiencing higher upskilling, while less developed countries experience deskilling. Technology, geographic level of analysis, sector and gender were also found to be important influences on human capital acquisition associated with international trade. Originality/value: Overall, the authors find support for the idea that trade with developing countries places pressure on low-skill jobs in developed countries but increases the demand for educated workers. The implications of shifts in skills for public policy-making and in terms of the skill premium on wages are discussed.